Preferential trade agreements between the monetary community of Central Africa and the European Union: Stumbling or building blocks? A general equilibrium approach - Ngeleza, Guyslain K.; Muhammad, Andrew (Wiley, 2015)
This paper uses a computable general equilibrium approach to simulate two opposing views describing regional trade agreements either as building blocks for or stumbling blocks to multilateral trade liberalisation. This study focuses on the regional trade agreement between the Economic and Monetary Community of Central Africa (CEMAC) and the European Union (EU). Results show that, although a regional trade agreement may slightly raise welfare among the members of the agreement, the cost to nonmembers can be high. The regional breakdown in our design considers 14 regions, allowing for country‐specific analysis for one least‐developed country (Democratic Republic of Congo) and one non‐least‐developed country (Cameroon). Multilateral liberalisation amplifies welfare gain for Cameroon. The Democratic Republic of Congo, with its weaker institutional capacity, is affected negatively. An EU‐CEMAC regional free trade agreement without multilateralism produces gains for both Cameroon and the Democratic Republic of Congo. Copyright © 2011 John Wiley & Sons, Ltd.